Translation and plurisemiotic practices: A brief history / Traduction et pratiques plurisémiotiques. Un bref parcours historique - Francis Mus (JoSTrans: The Journal of Specialised Translation)
In this contribution to our introduction to the special issue, I look at how and to what extent 'plurisemiotic practices' have gradually been integrated as objects of study in Translation Studies. Even if every act of communication is (and has always been) a plurisemiotic act, it is clear that this dimension has long been neglected in favour of logocentric approaches. From the 'cultural turn' at the end of the 1970s onwards, the plurisemiotic has become increasingly visible, and has given rise to stimulating and sometimes very diverse research projects, with many consequences, regarding both the validity of several key notions of traductology and the very definition of the discipline. Today, the research is still in development. In addition to the unequal distribution of centres of interest (some semiotic devices have been studied more than others), two heuristic challenges persist. Is it possible to develop a univocal conceptual vocabulary? How to account for the complex and simultaneous interaction of these different semiotic devices in an analysis?